Language and Psychosocial Functioning among Deaf Learners with and without Cochlear Implants. (8th September 2017) - Marschark, Marc; Machmer, Elizabeth; Spencer, Linda J; Borgna, Georgianna; Durkin, Andreana; Convertino, Carol
Abstract: Various studies have examined psychosocial functioning and language abilities among deaf children with and without cochlear implants (CIs). Few, however, have explored how relations among those abilities might change with age and setting. Most relevant studies also have failed to consider that psychosocial functioning among both CI users and nonusers might be influenced by having language abilities in both signed and spoken language. The present investigation explored how these variables might influence each other, including the possibility that deaf individuals' psychosocial functioning might be influenced differentially by perceived and actual signed and spoken language abilities. Changes in acculturation and quality of life were examined over their first year in college, together with changes in perceived and assessed language abilities. Students with and without CIs differed significantly in some aspects of psychosocial functioning and language ability, but not entirely in the directions expected based on studies involving school-aged deaf students. Participants' cultural affiliations were related as much or more to perceived language abilities as to the reality of those abilities as indicated by formal assessments. These results emphasize the need to consider the heterogeneity of deaf learners if they are to receive the support services needed for personal and academic growth.